Integrating environmental, nutritional, and economic dimensions in Food choices: A case study on legume vs. meat-based burger patties - Abhishek Dattu Narote; Andrea Casson; Valentina Giovenzana; Alessia Pampuri; Alessio Tugnolo; Roberto Beghi; Riccardo Guidetti (Journal of Agriculture and Food Research)
Addressing sustainability in modern food systems requires a multi-dimensional approach that considers environmental, nutritional, and economic aspects. This study applies Life Cycle Assessment (LCA) to analyze three burger patties (legume, chicken, and beef) across these dimensions, aiming to provide a holistic view of their impacts. While prior studies examined LCAs of plant-based meat and beef burgers with limited recipe data, this research expands on them by using commercial recipes for legume- and meat-based patties.Conventional functional units, such as mass and individual nutritional content, fall short in capturing the full nutritional value. To bridge this gap, a modified Nutritional Rich Food Index (NRF Index) was introduced, integrating multiple nutrients (e.g., vitamins, minerals, macronutrients) into a single nutritional functional unit (n-FU) that better represents the overall nutritional quality.Additionally, consumer purchase prices were incorporated to offer an economic perspective, and an economic functional unit (e-FU) was developed to assess the cost-effectiveness of each patty concerning their nutritional and environmental performance. This novel combination of functional units enables a more comprehensive evaluation, revealing trade-offs between sustainability dimensions. Results: highlight significant environmental disparities among the products, with beef demonstrating the highest Global Warming Potential (GWP) at 4.64 kg CO2 eq per 100 g, while the legume-based patty exhibited the lowest GWP at 0.113 kg CO2 eq. Affordability indices indicate that meat options may be more accessible to budget-conscious consumers despite their higher environmental impacts.This integrated assessment framework offers valuable insights for consumers and policymakers, supporting informed decisions that promote sustainable dietary choices aligned with nutritional and economic considerations.